The democratic risk society. Issue 9 (20th October 2016) - Greco, Pietro
Abstract : We live in what Ulrich Beck defined as a "risk society." This is not due to an increase in the number of risks for men compared with the past (on the contrary the rise in the average life expectancy seems to tell us the opposite) but because we have a "huge awareness" of risk. This awareness stems from our always deeper scientific knowledge of risk sources. However, this also leads to the fact that people who are not experts in this field want to have their say when it comes to risk management. Therefore, a democratic society needs a "new alliance" between scientists and citizens. The meeting of Ischia wants to testify, even if on a small scale, the beginning of such an alliance.